2015
DOI: 10.1364/oe.23.014351
|View full text |Cite
|
Sign up to set email alerts
|

MWP phase shifters integrated in PbS-SU8 waveguides

Abstract: Abstract:We present new kind of microwave phase shifters (MPS) based on dispersion of PbS colloidal quantum dots (QDs) in commercially available photoresist SU8 after a ligand exchange process. Ridge PbS-SU8 waveguides are implemented by integration of the nanocomposite in a silicon platform. When these waveguides are pumped at wavelengths below the band-gap of the PbS QDs, a phase shift in an optically conveyed (at 1550 nm) microwave signal is produced. The strong light confinement produced in the ridge waveg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Results were even improved by exploiting the better confinement of the light provided by the PbS-SU8 ridge structures [88]. Here, the QD-polymer active waveguides presented potential benefits with respect to other technologies, such as a continuous scan of the phase delay or its small size.…”
Section: -P13mentioning
confidence: 99%
See 1 more Smart Citation
“…Results were even improved by exploiting the better confinement of the light provided by the PbS-SU8 ridge structures [88]. Here, the QD-polymer active waveguides presented potential benefits with respect to other technologies, such as a continuous scan of the phase delay or its small size.…”
Section: -P13mentioning
confidence: 99%
“…Nevertheless, properties of perovskite look promising in these directions, since they not only present interesting light emitting properties but also a high electron mobility and diffusion lengths, already exploited to develop solar cells [88], LEDs [89,92] or photodetectors [90,91].…”
Section: -P17mentioning
confidence: 99%
“…Alternatively, third-order nonlinear effects in PNCs may also explain the experimental results presented here, at least to be considered as another phenomenological model until being confirmed by other different experiments. In previous works, we demonstrated that similar pumping conditions can change the effective refractive index of colloidal QDs integrated in plasmonic [44] or dielectric waveguides [48] due to a nonlinear interaction of pump plus probe beams with QDs. On the other hand, a Four Wave Mixing (FWM) third-order nonlinear process has been commonly proposed to provide parametric gain in Fiber-based optical devices [49] or the generation of high energy femtosecond pulses [50].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we observe waveguided photoluminescence under TPA in dielectric waveguides containing our CdSe/ZnS QDs (see Section S8.4 in the Supplementary Information). Furthermore, in similar PMMA-QD waveguides, we demonstrated that it is possible to induce a change in the effective refractive index of the mode at the signal frequency when the active medium is strongly and efficiently pumped at the pump frequency [49], in analogy of a four-wave mixing process [50]. This type of nonlinear modulation can be taken into account by adding an extra term proportional to I PUMP to the waveguide mode propagation constant at the signal frequency, due to the change of its effective refractive index.…”
Section: T C Andmentioning
confidence: 91%